Reading comprehension in high school students. A theoretical review (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article presents a reflective analysis of reading comprehension and its respective levels of concreteness in teaching, starting from an epistemological analysis proposed from the experiences of researchers as strategies for approaching each level with respect to the contextualization and exemplification of how it is strategically used in the classroom or in different school environments. The proposed objective is based on the bibliographic analysis of research on the application strategies used by researchers. The methodology used corresponds to an orderly exploration of hermeneutic type, through searches in databases: Scopus, Redalyc, Scielo, Dialnet. The search equations were "reading comprehension" AND "High school students"; "reading comprehension levels" AND "High school students". After filtering and screening, 21 articles were selected for analysis. The review explored conceptual generalities of the topic of study, the levels, strategies and skill development of each level of literal, inferential and critical reading comprehension.  It is concluded that reading comprehension develops critical thinking, nourishes knowledge, provides insertion to reading and allows the development of cognitive reasoning.